EKSPANSI MINISO JEPANG KE INDONESIA STUDI KASUS: PEKANBARU 2019-2020 - Sahri Rafika; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The phenomenon of Miniso's expansion is an interesting phenomenon to study, because in marketing its products Miniso first examines the market and consumers, and the products offered contain a "simple, natural and quality" philosophy. Miniso was present in Indonesia in 2017 and spread to all cities in Indonesia, one of which is Pekanbaru because they consider Pekanbaru to be a prospective city in the economic field so that it is easy to market their products.                        The perspective used in this study is Neoliberalism with an International System analyst level. This study uses Foreign Direct Investment (FDI) Theory which is able to explain the investment cooperation carried out by Japan in Indonesia in the case study of the Miniso Expansion in Indonesia, and the method used in this study is Qualitative methods with data collection techniques through primary data and secondary data.            This research was conducted at Miniso Plaza Citra Pekanbaru directly to the resource person, namely Supervisor Miniso, and to 40 participants for one month as a sample, in order to obtain concrete data about the development of Miniso in Pekanbaru city, especially Plaza Citra. The results showed that Miniso expanded to Pekanbaru because Pekanbaru is one of the most populous cities in Sumatra after Medan and Palembang and a city that has a rapid economic growth.Keywords: Miniso Expansion, Millennials, Japan, Indonesia, Pekanbaru